2007
DOI: 10.1007/s11664-007-0316-0
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Behavior of Sn-3.8Ag-0.7Cu Solder at Intermediate Strain Rates: Effect of Microstructure and Test Conditions

Abstract: When mobile electronic devices drop during service, solder interconnects are loaded under intermediate to high strain rates. Therefore, the strain response of solders at elevated strain rates is critical to reliability prediction. This paper presents the plastic flow behavior of Sn-3.8Ag-0.7Cu solder under compression over strain rates ranging from 0.1 s -1 to 30 s -1 at several different temperatures and under various aging conditions. Both yield strength and work hardening rate were observed to increase subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…4,12,15 These strain concentrations arise due to misfit strains induced via elastic-plastic mismatch between the solder and the IMC layer. 10,12,13 In addition, strain localization within the solder immediately adjacent to and parallel to the interface can cause stress concentrations in the scallops, enhancing the propensity for IMC fracture. 10 Therefore, a rougher IMC layer forces crack propagation either along the solder-IMC interface via microvoid nucleation and growth or through the IMC layer and/or the IMC scallops; all of these lead to low fracture toughness.…”
Section: Considerations For Defining Effective Imc Thicknessmentioning
confidence: 99%
See 1 more Smart Citation
“…4,12,15 These strain concentrations arise due to misfit strains induced via elastic-plastic mismatch between the solder and the IMC layer. 10,12,13 In addition, strain localization within the solder immediately adjacent to and parallel to the interface can cause stress concentrations in the scallops, enhancing the propensity for IMC fracture. 10 Therefore, a rougher IMC layer forces crack propagation either along the solder-IMC interface via microvoid nucleation and growth or through the IMC layer and/or the IMC scallops; all of these lead to low fracture toughness.…”
Section: Considerations For Defining Effective Imc Thicknessmentioning
confidence: 99%
“…The definition of the effective yield strength used for the FMMs is consistent with a number of reports showing a power-law dependence of solder yield strength on strain rate. 13,14 The formulation of t eff , on the other hand, was first proposed in Ref. 11, and the functional dependence of the fracture path on t eff was qualitatively validated based on observations on the solder-Cu system.…”
mentioning
confidence: 99%
“…2 Failure of the solder joint can mainly take place in two different modes: first, due to viscoplastic deformation accumulation and final failure in the bulk solder, and second, interfacial damage and crack growth causing fracture along the interface of the solder and the substrate. [4][5][6][7][8][9] Several experimental and theoretical investigations on the creep properties and viscoplastic nature of lead-free solders have led to good insight into this subject. 4,5,[10][11][12][13] However, comparison of the experimental results obtained in various studies shows considerable disagreement in several cases.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] Several experimental and theoretical investigations on the creep properties and viscoplastic nature of lead-free solders have led to good insight into this subject. 4,5,[10][11][12][13] However, comparison of the experimental results obtained in various studies shows considerable disagreement in several cases. Indeed, a review of identified constitutive parameters related to the hyperbolic sine model in different studies confirms the existence of wide scatter in the creep property database of the solders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation